Rights and Obligations of Citizens in the Constitutional Law System (International Forum of Researchers and Lecturers, 2025)
The definition of rights according to KBBI ( Dictionary Besar Bahasa Indonesia) is as authority, power to do (because it has been determined by certain laws or rules), and the right power to do something or demand something. The definition of rights in general is everything that is given to certain parties in certain situations... While according to the KBBI ( Dictionary Besar Bahasa Indonesia) obligation is (something) that must be done; must. These two concepts are very important for the life of the community, nation and state. The constitution in every country, including Indonesia, functions as a positive legal basis that regulates the rights and obligations of its citizens. The state grants rights to its citizens and citizens carry out and fulfill their obligations in the state. This journal will discuss the rights and obligations of citizens in the constitutional law system, as well as how they relate to and impact on society.